Codependency in Psychological Studies - Yu. V. Stryapukhina; S. T. Posokhova (СибСкрипт)
Codependency is an important psychological and clinical issue in the current socio-cultural environment. Despite the variety of scientific approaches, its definitions remain unsystematic and inconsistent. Codependency requires a systematic, integral model to cover all aspects of its manifestation. This review of the codependency phenomenon in modern psychology relied on the semantic content of codependency, as well as the key areas of life that set up predispositions for codependency development, correction, and prevention. The review covered 94 theoretical and methodological foreign and domestic research papers. The method of content analysis yielded a set of definitions that highlighted the semantic diversity of codependency as a cultural phenomenon, a value-semantic element, a personality deformation, a reaction of helplessness, a special mental state, a form of protective coping behavior, and destructive relationships with a dependent person. As a result, the authors defined codependency as a multidimensional, multifunctional, and dynamic clinical and psychological phenomenon when the person is so focused on the value of another person that starts to identify with them, which results in deformed self-attitude, poor goal-setting, and pathological adaptation in an adverse life situation. Codependency manifests itself at the psychophysiological, emotional, value-semantic, social, and behavioral levels. It requires a comprehensive clinical and psychological intervention. It emerges in the family as a form of social community and affects all its members. Codependency development and correction corelate with certain changes in intra-family relations.